PENGARUH KUALITAS PELAYANAN DENGAN KEPUASAN KONSUMEN PADA PT. PUSRI PALEMBANG PPD LAMPUNG - Sari, Yudiana (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract-The research object of this research is PT. PUSRI PPD Lampung Palembang. PT Pusri arranged subsidized fertilizer marketing services in specific areas (rayonisasi) and the Minister of Industry Decree 356 / MPP / Kep / 5/2004 for the smooth distribution of subsidized fertilizers which are the responsibility of manufacturers, authorized distributors and authorized retailers. The problem under study is to analyze the effect of service quality on customer satisfaction at PT. PUSRI Lampung Palembang PPD due to sales of PT. PUSRI PPD Lampung Palembang. The method used in this research is the research literature and field research conducted by examining directly on PT. PUSRI PPD Lampung Palembang. The results showed that the calculation formula product moment correlation that is equal to 0.804 with n = 55. The number is located on the interval coefficient of 0.75 to 1, which means the relationship between service quality and customer satisfaction in the volume of sales at PT. PUSRI Lampung Palembang PPD is very strong.